Concert and contest collection for C flute with piano accompaniment - VOXMAN, H. (Rubank, Inc., 1949)
Gavotte (3), Bergamask (4), Serenade (5), Scherzino (6-7), Valse Gracieuse (8-9), Andalouse (10-11),Menuet (12-13), Serenade (14), Siciliana and Giga (15), Menuetand Spirit Dance (16-17), Polonaise and Badinerie (18-19), Romance (20-21), Flight of the Bumblebee (22-23), Pan (24)